Peran Financial Attitude dan Financial Experience Terhadap Financial Management Behavior - Gunawan, Akhmad; Suyantiningsih, Tri; Salsabila, Firial Dhia (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This research is motivated by the still low ability of Micro and Small Enterprises (MSEs) to systematically manage their business finances, which impacts their weak long-term orientation, financial management behavior, and business performance. These problems are primarily related to limited financial experience and the suboptimal financial attitude in the practice of managing business finances. This study aims to analyze the influence of financial experience and financial attitude on the financial management behavior of culinary MSE owners in Bantul Regency, Yogyakarta Special Region. This study used a quantitative approach with a survey method by distributing questionnaires to respondents selected using random sampling techniques. Data were analyzed using multiple linear regression analysis with the assistance of SPSS software. The results show that financial experience has a positive and significant effect on the financial management behavior of cullinary MSEs. Conversely, financial attitude does not significantly influence financial management behavior. This finding indicates that the improvement of MSEs' financial management capabilities is influenced by practical experience and financial attitude. This research is expected to provide a theoretical contribution to the development of behavioral finance studies and serve as a basis for stakeholders' considerations in designing programs to increase the financial capacity of MSEs in a sustainable manner.